2023
DOI: 10.3390/molecules29010120
|View full text |Cite
|
Sign up to set email alerts
|

Selenium—More than Just a Fortuitous Sulfur Substitute in Redox Biology

Luisa B. Maia,
Biplab K. Maiti,
Isabel Moura
et al.

Abstract: Living organisms use selenium mainly in the form of selenocysteine in the active site of oxidoreductases. Here, selenium’s unique chemistry is believed to modulate the reaction mechanism and enhance the catalytic efficiency of specific enzymes in ways not achievable with a sulfur-containing cysteine. However, despite the fact that selenium/sulfur have different physicochemical properties, several selenoproteins have fully functional cysteine-containing homologues and some organisms do not use selenocysteine at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 348 publications
0
4
0
Order By: Relevance
“…Selenium is an extremely essential micronutrient that participates in multiple processes that are crucial for homeostasis maintenance. The positive role of this trace element takes place through its involvement in the structure of several enzymes known as selenoproteins, including GPx, thioredoxin reductase (TrxR), and iodothyronine deiodinase (Dio) acting predominantly as antioxidant defenses [ 64 , 65 ]. In general, the link between selenium-containing enzymes and proper reproductive functions is well established, and selenium deficiency is known to be responsible for many causes of female fertility impairment [ 65 ].…”
Section: The Impact Of Selected Antioxidants On Endometriosis-related...mentioning
confidence: 99%
“…Selenium is an extremely essential micronutrient that participates in multiple processes that are crucial for homeostasis maintenance. The positive role of this trace element takes place through its involvement in the structure of several enzymes known as selenoproteins, including GPx, thioredoxin reductase (TrxR), and iodothyronine deiodinase (Dio) acting predominantly as antioxidant defenses [ 64 , 65 ]. In general, the link between selenium-containing enzymes and proper reproductive functions is well established, and selenium deficiency is known to be responsible for many causes of female fertility impairment [ 65 ].…”
Section: The Impact Of Selected Antioxidants On Endometriosis-related...mentioning
confidence: 99%
“…These differences can be explained mainly by the bigger size and greater polarizability of the Se atom compared with sulfur (S). 37 Thus, Se bonds with hydrogen (H), carbon (C), or another Se atom present lower bond energies than their S counterparts. 38 The weaker Se−H bond accounts for the much lower basicity of selenolate feat thiolate, with acidic constants differences in the range of 3 to 4 orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Despite state-of-the-art treatments, their use is usually hampered by detrimental adverse effects, drug resistance, reduced treatment adherence, or decreased quality of life for patients. In this context, a large variety of studies have been carried out to ascertain the possible clinical application of a great variety of organoselenium compounds, as it has been reported that the inclusion of Se motifs into a wide range of active compounds endows them with enhanced physicochemical and biological properties. Studies regarding chalcogen isosteric replacements have gained great interest throughout the years as they are a feasible option for obtaining distinctive, safer, and more effective drug candidates with improved biopharmacological profiles compared to the parent compounds. Although chalcogens display similar physicochemical properties, they exhibit different chemical reactivity, mainly related to their acidity, redox potentials, electrophilicity, and nucleophilicity. These differences can be explained mainly by the bigger size and greater polarizability of the Se atom compared with sulfur (S) . Thus, Se bonds with hydrogen (H), carbon (C), or another Se atom present lower bond energies than their S counterparts .…”
Section: Introductionmentioning
confidence: 99%
“…The crucial cysteine both coordinates Ni and serves as a H + mediator. An attractive approach for probing the role of a cysteine-S atom is to exchange the cysteine for a selenocysteine (Sec, one-letter code U) by recombinant methods. Selenium is only slightly larger than sulfur, and has a similar electronegativity, but its proton affinity is much lower; this property is passed on to Sec, for which the p K a of the free amino acid is 5.2 compared to 8.3 for Cys. In a notable subclass of [NiFe]-hydrogenases, the same cysteine is replaced by selenocysteine: compared to standard [NiFe]-hydrogenases, [NiFeSe]-hydrogenases have higher activity for proton reduction with very little product (H 2 ) inhibition. We recently used PFE to investigate the consequences of replacing each of the four Cys coordinating the Ni, by Sec, in the O 2 -tolerant Hydrogenase-1 (Hyd-1) from E. coli .…”
mentioning
confidence: 99%